65.3: Phase‐Modulation LCoS Display System with Off‐Axis LED Reconstruction Light. Issue 1 (1st July 2013) - Liao, Li‐Yuan; Chen, Cheng‐Huan; Chen, Fu‐Hao; Tsai, Chao‐Hsu; Liao, Engle; Hong, Sylvia
Abstract: A near eye holographic display using light‐emitted diode (LED) instead of laser diode as the reconstruction light source has been proposed. An off‐axis illumination architecture on a phase modulation only liquid crystal on silicon(LCoS) panel is used for investigating the influence of LED source property on the reconstruction image quality.